Interactive Web-Based Education: A Multimedia-Mediated Web Learning (MMWL) Framework - Neo , Mai (2005)
This research project seeks to explore the impact of the various learning environments using the Web and multimedia technologies on student learning and the learning process. Five learning environments or LEN types were designed and developed based on the various teaching and learning strategies to promote learning in problem-solving, critical and analytical thinking skills, teamwork and collaborative learning as well as communication and presentation abilities.